La sperimentazione astratta nella fotografia di Paolo Monti (1950-1970) - Zannelli, Diletta (Rivista di studi di fotografia. Journal of Studies in Photography, 2016)
This paper presents a study on the experimental works of Paolo Monti (1908-1982), characterized by a constant investigation on the language of abstract photography in dialogue with major art movements such as Abstract Expressionism, Informel, Spatialism, and Nouveau Réalisme. A key  gure in the history of the late-2oth century Italian photography, Monti has interpreted the artistic and intellectual ferment of his time in innovative and unique ways, contributing to photography’s full recognition in the larger  eld of contemporary art.